Acid-treatment of bio-oil in methanol: The distinct catalytic behaviours of a mineral acid catalyst and a solid acid catalyst - Wu, L.; Hu, X.; Wang, Shuai; Mahmudul Hasan, M.; Jiang, S.; Li, T.; Li, C. (Elsevier Ltd, 2018)
© 2017 Elsevier Ltd The different catalytic behaviour of solid acid catalyst and mineral acid catalyst towards the acid-treatment of bio-oil was investigated. The hydrogen ions in the mineral acid catalyst such as sulfuric acid homogeneously dispersed in the reaction medium made the conversion of main components of bio-oil including carboxylic acids, sugars and phenolics more efficient. In comparison, there was a steric hindrance for these components of bio-oil to access the hydrogen located in the local surface of the solid acid catalyst such as Amberlyst 70. This negatively affected their conversions during the acid-treatment. However, the inhomogeneous distribution of hydrogen ions from Amberlyst 70 in the reaction medium created high concentration of hydrogen ions in the local vicinity of the solid catalyst surface of the catalyst, which is found to be crucial for the occurrence of the etherification reactions. Understanding how the dispersion of hydrogen ions of catalyst affect the esterification of bio-oil can provide useful information for the development of the effective catalysts for upgrading of bio-oil.